Design Data Warehouse for Medical Data - Jaber, Mustafa Musa (2010)
Organizing and managing the database relations in term of data warehouse technology has been addressed widely in different complex environments. The data warehouse contains a source of valuable data mining. The data contained in the data warehouse is cleaned, integrated, and organized. This study highlighted the existing issues on the medical databases which present a huge number of information across various departments, managing this type of data require time, and laborious tasks to separately access and integrate reliably. Hence, this study aimed to model new medical data warehouse architecture for managing and organizing the medical dataset operation into data warehouse. Technically OLAP has been used to design the proposed architecture, for the hospitable administrators, and top manager and/or sophisticated user can use MDW by using Microsoft SQL Server 2005. Building the proposed architecture adopted by using Microsoft Visual Studio for performing the OLE database operations. The performing process has been tested through the using of use test case technique.